2007
DOI: 10.1242/dev.002709
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of skeletogenic differentiation in cranial dermal bone

Abstract: Although endochondral ossification of the limb and axial skeleton is relatively well-understood, the development of dermal (intramembranous) bone featured by many craniofacial skeletal elements is not nearly as well-characterized. We analyzed the expression domains of a number of markers that have previously been associated with endochondral skeleton development to define the cellular transitions involved in the dermal ossification process in both chick and mouse. This led to the recognition of a series of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
167
1
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 199 publications
(188 citation statements)
references
References 76 publications
13
167
1
7
Order By: Relevance
“…Bmp4 expression around the pnc is known to cause a marked expansion of this skeletal tissue, as exemplified in L. noctis (Fig. 3) and in previous studies (9,11,21). However, Bmp4 is primarily expressed in the pmx of stage 30 L. violacea and L. portoricensis embryos, and therefore the pnc of these two species does not expand (compare their pnc with that of L. noctis in Fig.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Bmp4 expression around the pnc is known to cause a marked expansion of this skeletal tissue, as exemplified in L. noctis (Fig. 3) and in previous studies (9,11,21). However, Bmp4 is primarily expressed in the pmx of stage 30 L. violacea and L. portoricensis embryos, and therefore the pnc of these two species does not expand (compare their pnc with that of L. noctis in Fig.…”
Section: Resultssupporting
confidence: 53%
“…To establish which molecules regulate the pmx in L. violacea and L. portoricensis, we examined the expression of other skeletogenic factors known to control avian craniofacial development (18)(19)(20)(21). We found that in these two species, early in development Bmp4 is primarily expressed in domains coinciding with their developing pmx (compare the bone condensation in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sox9 is a well-known marker for chondrogenic cells in the process of endochondral ossification, but it also plays an important role in the differentiation of CNCCs to early bone progenitor cells during intramembranous ossification [19]. Accordingly, we detected the elevated levels of Sox9 expression during the early phase of the osteogenic differentiation, which then decreased below the initial level at the later stages of the culture process ( Figure 3B).…”
Section: Discussionmentioning
confidence: 68%
“…These findings indicate there is no chondrogenic tissue formation and the osteogenic differentiation is through the intramembraneous course. Early phases of the osteogenesis process are directly regulated by Runx2, an early marker and regulator of many other osteoblast markers, such as Bsp, Ocn and Alp [19]. In our 3-D differentiation system, RUNX2 was expressed during the first week of osteogenesis and its expression decreased significantly at the later stages of bone tissue culture ( Figure 4G).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation